2018
DOI: 10.1128/jvi.00753-18
|View full text |Cite
|
Sign up to set email alerts
|

An N-Glycosylated Form of SERINC5 Is Specifically Incorporated into HIV-1 Virions

Abstract: SERINC5 is an inhibitor of retroviral infectivity that is counteracted by viral proteins, including HIV-1 Nef. Inhibition of infectivity by SERINC5 is associated with its incorporation into virions. Nef counteracts this inhibition, presumably by removing SERINC5 from sites of virion assembly at the plasma membrane. While evaluating the virion incorporation of SERINC5, we observed that a relatively high molecular weight form was preferentially present in virions. We used various glycosidases to establish that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 41 publications
8
32
0
Order By: Relevance
“…2B and C, which show representative results of an experiment in which Jurkat cells were used to produce virions and quantitative data from three experiments). We confirmed that a 55-kDa form of SERINC5, while the minority species in cells, is the predominant form in virions, an effect due to the selective incorporation into virions of a form of the protein modified by complex glycans (58). The quantitative data suggested that the ΔEDTEE mutant was slightly less efficiently incorporated into virions than wild-type SERINC5 in the absence of Nef; the data also indicated that the ΔEDTEE mutant was excluded from virions by Nef about 2-fold more efficiently than wild-type SERINC5 ( Fig.…”
Section: Resultssupporting
confidence: 70%
“…2B and C, which show representative results of an experiment in which Jurkat cells were used to produce virions and quantitative data from three experiments). We confirmed that a 55-kDa form of SERINC5, while the minority species in cells, is the predominant form in virions, an effect due to the selective incorporation into virions of a form of the protein modified by complex glycans (58). The quantitative data suggested that the ΔEDTEE mutant was slightly less efficiently incorporated into virions than wild-type SERINC5 in the absence of Nef; the data also indicated that the ΔEDTEE mutant was excluded from virions by Nef about 2-fold more efficiently than wild-type SERINC5 ( Fig.…”
Section: Resultssupporting
confidence: 70%
“…4g-i). The disulphide bonds and the location of ECL4, the equivalent of which harbours glycosylated Asn294 in SERINC5 22 , confirms the assigned orientation within the plasma membrane, with both the N-and C-termini of the protein residing in the cytoplasm (Fig. 1b, Supplementary Table 1 and Extended Data Fig.…”
Section: Structure Determination Of Drosophila Melanogaster Serincsupporting
confidence: 62%
“…Arrowheads and asterisks indicate migration position of glycosylated and non-glycosylated SERINC5, respectively. Note the selective incorporation of the glycosylated form into viral particles 22 d, Class 1 and 2 residues mapped onto a model of SERINC5, in red and blue, respectively. e, Neutralisation of Nef-deficient HIV-1 NL4-3 carrying the JRFL envelope by 2F5 and 4E10 monoclonal antibodies.…”
Section: Extended Datamentioning
confidence: 99%
“…Additionally, we noticed that in cells in which Gpr176 was overexpressed, a minor fraction of the WT proteins migrated at approximately 50 kDa ( Fig. 2B; open arrowhead), which possibly reflects the presence of immature or less glycosylated proteins, as reported for other GPCRs and non-GPCR glycoproteins that have been overexpressed [33][34][35][36] .…”
supporting
confidence: 57%